Research trends in Australia and New Zealand Nephrology: basic science and gender equity in peril. Issue 11 (8th November 2022) - Purvis, Megan R.; Robertson, Harry; Patrick, Ellis; Rogers, Natasha M.
Abstract: Basic science research remains fundamental to progress in clinical care, understanding of disease pathophysiology and underpinning the evolution of personalised medicine. Exposure to research is pivotal to educating students, but a declining profile of basic science research has the potential to erode research capacity further. The capacity for women to engage in research and remain in academia long term is continually challenged by negative gender‐based experiences and institutional barriers. The authors explored themes and authorship of abstracts presented at Australia and New Zealand–‐based nephrology conferences, as a surrogate marker of trends in research activity and gender engagement. Basic science research and female senior authorship declined during the study period, which has serious implications for the future of nephrology.